Ethanolic extract of Dutch eggplants (Solanum betaceum) protects spermatozoa motility exposed to lead acetate - Rima Wirenviona; Reny I'tishom; Siti Khaerunnisa (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2020)
Lead is a toxic material that can have negative effects on reproductive organs. Lead exposure reduces the activity of endogenous antioxidant enzymes and increases the number of oxidants in the body. High free radicals will affect spermatogenesis and result in decreased motile spermatozoa. Antioxidants are known to protect the motility of spermatozoa, and adequate antioxidants can be found in Dutch eggplants (Solanumbetaceum). This study aimed to evaluate the effect of S. betaceum on spermatozoa motility after exposure to lead acetate. This study is a true experimental design with a randomized post-test-only control group design. Forty male Balb/C mice 12 weeks old were randomly divided into 5 groups: two control groups (C0, C1) and three treatment groups (T1, T2, T3).The C0 received distilled water, and the C1 received 75 mg/kg BW lead acetate. The T1, T2 and T3 received 100, 200 and 400 mg/kg BW of S. betaceum, respectively, an hour before exposed lead acetate. The data were analyzed using one-way ANOVA with a significant level of p <0.05. A significantly increasein the mean total motility of spermatozoa in T1, T2, and T3 was reported.This study indicates that S. betaceum have a protective effect on spermatozoa motility when exposed to lead acetate.